‘I wish something would happen to you, my friend!’ Tourism and liberalism in E.M. Forster's Italian novels - Sampaio, S. (2012)
In this article, I look at E.M. Forster's treatment of tourism in his Italian novels, Where Angels Fear to Tread (1905) and A Room with a View (1908), by taking the figure of the tourist as a trope for the (English) liberal. Through a close reading of these works, and inspired by Pierre Macherey's A Theory of Literary Production (1978), I focus on these novels’ gaps and contradictions. My analysis endorses James Buzard's (1993) contention that Forster's position towards tourism is one of ‘internal distance’. Forster did move beyond the facile guidebook satire, revealing awareness of the pitfalls that attend to the quest for (unmediated) authenticity. Nevertheless, I reject Buzard's postmodernist premises and conclusions. Drawing on Alain Badiou's distinction between ‘being’ and ‘event’ (2005), I argue that Forster's take on tourism evolved towards the latter: if his first tourist novel is still interested in issues of identity, i.e. in depicting tourism as the site where Englishness is constructed in stark opposition to the Italian ‘Other’, his second novel illustrates the occurrence of an ‘event’. Exploring the parallels between tourism and the political culture of liberalism (to which Forster was so closely attached), I conclude with a reflection on the political implications of this shift.